2015
DOI: 10.4236/aim.2015.56042
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacterial Fish Pathogens in Brazil by Direct Colony PCR and 16S rRNA Gene Sequencing

Abstract: Intensive fish farming systems in Brazil have increased the disease incidence, mainly of bacterial origin, due to higher stocking density, high organic matter levels and poor quality of the aquatic environment that causes high mortality rates during outbreaks. The identification of pathogenic species using a fast and reliable method of diagnosis is essential for successful epidemiological studies and disease control. The present study evaluated the use of direct colony PCR in combination with 16S rRNA gene seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 31 publications
2
36
1
9
Order By: Relevance
“…Furthermore, the addition of ethanolic extract of propolis to tilapia diets has shown to promote growth, immunity, as well as resistance to Aeromonas hydrophila (Abd-El-Rhman 2009), a gram negative opportunist bacterium that affects a wide variety of freshwater fish species and causes tail and fin rot, hemorrhagic septicemia and epizootic ulcerative syndrome (Lu 1992). A recent study has shown that this bacteria is the most common and important tilapia pathogen in Brazil (Sebastião et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of ethanolic extract of propolis to tilapia diets has shown to promote growth, immunity, as well as resistance to Aeromonas hydrophila (Abd-El-Rhman 2009), a gram negative opportunist bacterium that affects a wide variety of freshwater fish species and causes tail and fin rot, hemorrhagic septicemia and epizootic ulcerative syndrome (Lu 1992). A recent study has shown that this bacteria is the most common and important tilapia pathogen in Brazil (Sebastião et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They have also been observed in Brazilian fish farms over a wide geographic distribution and range of hosts (Evans, Klesius & Shoemaker ; Sebastião et al . ), so the disease could pose a worldwide problem for fish farming, particularly in intensive culture systems.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular identification was performed using the primers 8F (5′‐AGAGTTTGATYMTGGCTCAG‐3′) and 907R (5′‐CCGTCAATTCMTTTRAGTTT‐3′), following the method described in Sebastião et al . ().…”
Section: Methodsmentioning
confidence: 97%